Pembedayaan Masyarakat Melalui Usaha Ecoprint Dalam Upaya Pengembangan Ekonomi Masyarakat di Kampung Sabbeta Desa Pising Kecamatan Donri-Donri Kabupaten Soppeng - Munawwarah; St. Aisyah BM (Universitas Islam Negeri Alauddin Makassar, 2023)
The type of research used is descriptive qualitative research which is carried out by examining deeply a problem which then the results will be described. The approach method used in this research is a sociological approach and the data collection is done by means of observation, interviews, and documentation. The data sources in this study are divided into two types including primary data sources consisting of 5 people, while secondary data sources come from relevant documents. Researchers also use purposive sampling techniques where researchers select informants according to criteria and have a close relationship in the study. The data analysis technique carried out has three stages, namely data reduction, data presentation and conclusion drawing. The results showed that: 1) The process of community empowerment through ecoprint business in an effort to develop the community's economy in Sabbeta Village includes the preparation stage, assessment stage, alternative program planning stage, formulation stage, and program implementation stage, then 2) The results of community empowerment through ecoprint business are increased knowledge and skills, job creation, increased income, and preservation of local culture.